Sustainable Energy Policy Reform through Computational Simulations of Carbon Pricing Financial Stability and Environmental Outcomes - Rudransh Kohli (Journal of Daoist Studies, 2026)
This paper examines the sustainable energy policy reform through the large-scale computational simulation of the dynamic interaction between carbon pricing, economic outcomes and environmental outcomes. The study also considers the effectiveness of various policy instruments such as carbon taxes, renewable energy subsidies and market-based price mechanisms in transforming carbon emission, energy price and economic development pathways with the application of system dynamics, econometric, and agent-based modelling. The findings indicate that renewable energy endogenous technological change, in combination with carbon price mechanisms such as the coal cess, can provide massive CO 2 reduction with no negative impact on the growth rate. In addition, a well synchronized combination of carbon emission trading (CET) and policies in support of renewable energy, further makes the change in energy efficient, makes the process less expensive and the process of using renewable energy is faster. Evidence of the critical nature of an alternative such as the computational modelling as a policy support mechanism is also noted, ensuring the production of evidence-based decision-making towards the creation of energy transition policies that will not only drive sustainability goals, but also conditions of economic stability. The results lead to the conclusion that the optimal approach to emissions reduction, increasing the proportion of renewables, and allowing the economy to develop is through the high coordination of carbon pricing, new technologies, and renewable energy policies. The computational models provide the policy makers with solid foundation on which to include the long-term impact of energy transitions, to ensure that sustainability and macroeconomic performance of the economy is achieved.